Leaning Meanings in Bima Language: A Study of Natural Semantic Metalanguage - Adawiyah, Rabiyatul (Universitas Pendidikan Mandalika, 2023)
The study of regional languages is a critical component of a nation's cultural and linguistic heritage. As such, it is imperative to conduct in-depth research into the meanings and nuances of regional languages. In this study, the Bima language (ngahi mbojo), which belongs to the Bima-Sumba language family and is widely spoken in the Bima and Dompu districts, was examined to map and explicate verbs with the concept of 'lean'. To gather the necessary data, oral and written sources were used, including storybooks in the Bima language. The research methodology utilized a combination of interviews and literature review, while the verification method was employed to collect and analyze the data. The method, which involves the alteration of form and the use of paraphrasing techniques, was utilized to determine the original meaning of the verb and its explication, resulting in 65 points of analysis. The study revealed that Bima language verbs with 'lean' can be mapped to entities, processes, tools, and results. Specifically, the lexicon used to express the concept of 'leaning' includes maru (sleeping), santengi (leaning), doho (sitting), oko (squatting), kidi (standing), and tu'u (getting up).